Identification and optimization of production bottleneck in a deviated oil well: a case study using nodal analysis - Raoof, Bafren Kamel; Al-Khafaji, Hussein Jasim; Muhammed, Salimah A.; Salih, Ali Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Hydrocarbons play a substantial role in the energy industry; however, maintaining a steady and optimal production rate in deviated wells remains a significant challenge, especially due to flow bottlenecks that reduce output efficiency. This study focuses on identifying and resolving production constraints in a deviated well located in the TK oil field in North Iraq with a total measured depth of 9639.5 ft. The true vertical depth is at 8137 ft. at an inclination angle of 39.90o. The well failed to meet the pre-evaluated rate of 1044 STB/D based on the current conditions. To accomplish the optimum rate, the deviated well S17 is subjected to nodal analysis and various possible alterations in the well geometry and production system. The nodal analysis through the Inflow Performance Relationship and Vertical Lift Performance characteristics is addressed utilizing IPM suites Prosper to replicate the flow in the tubing through integrated correlations, the fluid behavior, and the phase envelope. The saturation pressure is tuned with the correlations in the PVTp program. Different scenarios were set, such as the change in wellhead pressure, tubing internal diameter, reservoir pressure, skin factor, and the introduction of artificial lift. Following the simulation, as referred to previously, the detailed analysis of the variables provides an exhaustive insight for the field operators. The key finding of this well is that reducing skin factor and alongside the use of Electrical submersible pump (ESP) installation, significantly enhance production feasibility and the well will be able to produce when the reservoir pressure drops to 1500 psi These results provide actionable insides for field operators to improve production performance in similar well conditions.